Induced Spawning Of Selais Fish (Ompok hypopthalmus) Under Different Doses Of Human Chorionic Gonadotropin Hormon (hCG) - ', Nuraini; Alawi, Hamdan; Asiah, Nur; Priyatama, Adityo Tri (Jurnal Perikanan dan Kelautan, 2012)
The study was conducted to evaluate the best effect of Human ChorionicGonadotropin Hormon (hCG) doses (800, 1000, and 1200 IU/Kg body weight offemale on breeding performance of selais fish (O. hypopthalmus) under alaboratory condition. The breeding performance was judged on the base of thetotal weight of stripped eggs, fertilization rate, hatching and survival of 6 days oldfry were considered.The results indicated that the total weight of stripped eggs were the highestwhen females were injected with 1200 IU/Kg body weight (45 eggs/g of female)compared to those injected with 1000 IU/Kg and 800 IU/Kg of body weight.Percentages of total fertilized eggs and hatching were 41,58% and 31,94%respectively, which were the highest among treatments. The highest net survivalof 6 days old fry was found to be 97,24% at 800 IU/ Kg weight of female.